Spatiotemporal transcriptome atlas reveals the dynamic cellular and molecular characteristics of ovule development in gymnosperms - Min Jiang; Tao Jin; Dongming Li; Zhiping Song; Yuguo Wang; Wenju Zhang; Ji Qi; Ji Yang (Proceedings of the National Academy of Sciences, 2026)
Ovule, as the developmental precursor to seed, represents a key evolutionary innovation in seed plants. However, its origin and evolutionary trajectory have been debated for over a century, largely due to the disconnects between morphological information gained from fossils and the regulatory mechanisms of ovule development inferred from extant angiosperms. The core regulatory networks shared by gymnosperms and angiosperms may serve as a bridge in terms of the ovule developmental process. We employed spatial transcriptome sequencing to profile dynamic gene expression during ovule development in four representative gymnosperm species ( Ginkgo biloba , Gnetum montanum , Pinus tabuliformis, and Cycas panzhihuaensis ). Our analyses reveal distinct trajectories of cell-type differentiation during formation of tissues, uncovering critical genes and pathways involved in ovule primordium initiation, chalaza formation, and subsequently development of integument and nucellus. The spatiotemporal expression patterns of key regulatory genes, particularly those associated with proximal–distal (PD) polarity establishment, strongly support the hypothesis that early formed chalaza regions function as a meristematic zone, giving rise to the formation of integument and nucellus in a manner reminiscent of the shoot apical meristem activity. Moreover, gene expression patterns in the developing integument reveal well-defined PD and adaxial–abaxial polarity highly conserved across gymnosperm lineages. These findings suggest that integument development originated through the recruitment of preexisting regulatory networks into a core developmental module, providing clues for understanding the molecular mechanisms of integument formation underlying the origin of seed plant ovules.